“Cultoras del arte musical” : Music and cultural consumption of girls and women of the bourgeoisie of Rosario, 1870-1920 - Yunis, Micaela (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2018)
From the new questions that, from the social and cultural history, make focus on consumption in an expanded sense, this paper seeks to inquire into the cultural consumption linked to the music of women and girls in Rosario between the end of the 19th century and the first decades of the 20th. In the context of a society characterized by the mercantilism of its port and commercial activity, but eager to demonstrate its modern character, the local bourgeois families were able to find in the musical education of their girls and young women, an element of distinction and social prestige. In this way, becomes relevant the phenomenon of an important cultural consumption associated with music, that in the city was translated into the opening of several music conservatories that provided a careful preparation in this art, houses of music offering a variety of musical instruments, advertisements for private music lessons, and concerts and musical charity galas as spaces for showcasing the acquired skills. Another different aspect to analyze, but in close connection, is the attendance to theater, to a lyric gala or other shows with prestigious artists. Beyond being a consumption related to entertainment, theater attendance also had a special meaning in terms of visibility and social prestige, that occasionally could mean a better position in the networks of sociability of the local bourgeoisie.